2022
DOI: 10.4103/jfmpc.jfmpc_268_21
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction among medical officers working in Delhi

Abstract: Background: Satisfied human resource is an essential asset for high productivity, efficiency, and quality of care in a healthcare organization. Job satisfaction among healthcare professionals assumes further significance for the purpose of maximization of human resource potential in the context of the shortage of manpower in the health sector in India. Objectives: The objective of the study was to assess the job satisfaction among medical officers (MOs) working in Delhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Consistent with a number of studies, most (76%) of the healthcare professionals were not satisfied with their wage studies (Akuffo et al 2021 ; Anand et al 2022 ; Asegid et al 2014 ; Ayalew et al 2019 ; Khunou & Davhana-Maselesele 2016 ; Kumar et al 2013 ;). Khunou and Davhana-Maselesele ( 2016 ) stated that since the implementation of Occupational Specific Dispensation (OSD), no studies were conducted regarding the impact of this policy on the level of job satisfaction among healthcare professionals.…”
Section: Discussionsupporting
confidence: 64%
“…Consistent with a number of studies, most (76%) of the healthcare professionals were not satisfied with their wage studies (Akuffo et al 2021 ; Anand et al 2022 ; Asegid et al 2014 ; Ayalew et al 2019 ; Khunou & Davhana-Maselesele 2016 ; Kumar et al 2013 ;). Khunou and Davhana-Maselesele ( 2016 ) stated that since the implementation of Occupational Specific Dispensation (OSD), no studies were conducted regarding the impact of this policy on the level of job satisfaction among healthcare professionals.…”
Section: Discussionsupporting
confidence: 64%
“…This result showed that job satisfaction level among healthcare setting staff in Ethiopia was lower than [21]. On the other hand, job satisfaction level in Ethiopia healthcare settings was higher than Iranian nurses (46.3%) [16][17][18][19][20]. The above-mentioned differences in the level of satisfaction among healthcare setting workers may be variations in work autonomy, training opportunity, organizational policy, reward/recognition, payment scheme, adequate supervision and working environment.…”
Section: Discussionmentioning
confidence: 99%
“…So far, staff satisfaction studies among healthcare workers on different parts of the world showed different levels of satisfaction from country to country and discipline to discipline. Staff satisfaction level among United States (US) healthcare workers, Delhi medical officers, French doctors, the Netherlands' midwives and Iranian nurses was 77.6%, 59.1%, 64%, 100% and 46.3% [16][17][18][19][20], respectively. Staff satisfaction level among African healthcare workers was 52.1% in South Africa, 71% in Malawi, 82.6% in Tanzania and 62% in Kenya and Ghana [21].…”
Section: Introductionmentioning
confidence: 99%